Makna Esoteris Ayat Ibadah - Laila Sari Masyhur (Program Pascasarjana IAIN Langsa, 2021)
Al-Alusi's Ruh Al-Ma’ani is a book of commentary that combines the external (exoteric) and mental (esoteric) dimensions in the inner verses of the Qur’an. This paper examines the implementing of Isyari approach in his magnus opus (Ruh al-Maani) with references to the interpretation of worship verses. First of all, the author describes the theorizing of isyari approach in understanding the meaning content of the verses of the Qur'an. Then, the author describes the topography of the verses which are interpreted Isyari in the book of Ruh al-Ma’ani. The presentation then focuses on discussing the practice of interpretation using the Isyari method in the book of Ruh al-Ma’ani with references verses related to prayer, fasting, zakat and hajj. The article ends with a conclusion that emphasizes the view that al-Alusi's interpretation of the verses of worship using the Isyari method as done by al-Alusi is not in a position that contradicts the outer and inner dimensions of these verses.